2019
DOI: 10.5114/ceji.2019.89592
|View full text |Cite
|
Sign up to set email alerts
|

A study of the utility of novel non-invasive urinary and serum biomarkers of blunt kidney injury in a rat model: NGAL, KIM-1, and IL-18

Abstract: This study investigated changes in the concentrations of serum and urine neutrophil gelatinase lipocalin (NGAL), kidney injury molecule 1 (KIM-1), interleukin 18 (IL-18), and cystatin-C (Cys-C) induced by parenchymal and tubular damage following blunt kidney trauma, as well as their potential utility as biomarkers in the detection and follow-up of patients with suspected blunt renal trauma. Three-month-old male Sprague-Dawley rats (n = 18) were divided into three groups (n = 6 in each): group 1: control group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…For example, urine IL-18 combined with KIM-1 is considered to have the best diagnostic value for AKI that already exists, and urine NGAL combined with IL-18 is the best marker for the diagnosis of early AKI, while urine Nacetyl-beta-glucosamynidase combined with KIM-1 and IL-18 is an ideal marker for the prognosis of AKI. 21 , 22 In this study, the ROC curve showed that the combined marker of IL-18, NGAL and KIM-1 at hour 12 had the largest AUC for the diagnosis of AKI with the best sensitivity and specificity, which was helpful for the early diagnosis of AKI caused by sepsis. Urine collection can be performed at 12 h after URL to assess AKI risk.…”
Section: Discussionmentioning
confidence: 60%
“…For example, urine IL-18 combined with KIM-1 is considered to have the best diagnostic value for AKI that already exists, and urine NGAL combined with IL-18 is the best marker for the diagnosis of early AKI, while urine Nacetyl-beta-glucosamynidase combined with KIM-1 and IL-18 is an ideal marker for the prognosis of AKI. 21 , 22 In this study, the ROC curve showed that the combined marker of IL-18, NGAL and KIM-1 at hour 12 had the largest AUC for the diagnosis of AKI with the best sensitivity and specificity, which was helpful for the early diagnosis of AKI caused by sepsis. Urine collection can be performed at 12 h after URL to assess AKI risk.…”
Section: Discussionmentioning
confidence: 60%
“…Proximal tubule damage causes an increase in the concentration of NGAL in the urine, while damage to the distal part of the nephron causes increased synthesis and release of NGAL into the blood and the urine [13]. NGAL is a well-known diagnostic and prognostic marker of AKI [13][14][15] and chronic kidney disease (CKD) [16]. The clinical usefulness of NGAL has been demonstrated in systemic infections [9], including urinary tract infections (UTI) in children [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The correlation coe cient (R) between the Gal-3-TRFIA assay and commercially available enzyme-linked immunosorbent assay kits was 0.83. KIM-1 [19,20] and TIM-3 [21] were also found to be elevated in a variety of nephropathy and were selected as potential interferers for the test, which showed no effect on the measured Gal-3 concentration. Serum Gal-3 levels are negatively correlated with renal function.…”
Section: Discussionmentioning
confidence: 99%